Retrospective study of spontaneous bone regeneration after decompression of large odontogenic cystic lesions in children - Pejović, Marko; Stepić, Jelena; Marković, Aleksa; Dragović, Miroslav; Miličić, Biljana; Čolić, Snježana (Vojnosanitetski pregled, 2017)
Background/Aim. Surgical treatment of odontogenic cysts in childhood could be accompanied by injury of important anatomical structures. Even though enucleation is considered to be preferable treatment of odontogenic cysts, the specificities of pediatric age favor more conservative surgical approach. The aim of this study was to assess the effectiveness of decompression as the uttermost treatment of odontogenic cysts in the pediatric age. Methods. This retrospective study included 22 patients, 7−16 years old, with a single jaw cystic lesion. The majority of these lesions were dentigerous cyst (14), and the rest belonged to keratocystic odontogenic tumor (KCOT) (8). All lesions were primarily treated with decompression; it was a final treatment (one-stage procedure) in 13 dentigerous cysts, and it was followed by enucleation (two-stage procedure) in one dentigerous cyst and all the KCOT. Results. A total of 13 (59.1%) dentigerous cysts were treated successfully only with decompression as one stage procedure, while the other 9 (40.9%) cysts required enucleation (1 dentigerous and 8 KCOT), after decompression (p ≤ 0.001). Conclusion. Related to non-aggressive lesions, more conservative treatment approach, such as decompression as one-stage procedure, should be considered. On the other hand, KCOTs in children require a two-stage procedure for a successful treatment outcome.